(untitled) (Journal of Economic Research & Business Administration, 2018)
This article presents an economic analysis of trade and investment relations between the countries belonging to the EAEU. The purpose of the study is to assess the impact of trade and investment cooperation of the EAEU countries on the development of their economies. The significance of the work is manifested in mathematic analyze of the problems of foreign trade policy of our country in the context of economic integration. The method of investigation is an analytical grouping, comparison of dynamic series, construction of linear graphs and construction of a correlation model, which made it possible to determine the presence, direction and form of the relationship between the parameters considered. On the basis of the analysis of the model of multiple correlation, the author determined a very high degree of interrelation between the trade and investment cooperation of all three countries and the growth of their GDP before the creation of a customs union. However, between 2011 and 2016, relations between Kazakhstan and Russia increased when Belarus became more independent in this area. Trade and investment relations between Russia and Kazakhstan have a very strong influence on the development of the country’s economy, moreover, the influence grows with each period. The results confirm the mutual influence and dependence between Kazakhstan, Russia and Belarus, which also means the vulnerability of these countries to external negative influence. This is the main reason for creating an integration union.